In vitro and in vivo anticancer activity of steroid saponins of paris polyphylla var. yunnanensis - Yan, L.L; Zhang, Y.J.; Gao, W.Y.; Man, S.L.; Wang, Y. (Experimental Oncology, 2009)
Aim: To confirm the anticancer activity of steroid saponins isolated from the rhizome of Paris polyphylla var. yunnanensis and evaluate the structure-activity relationships of these steroid saponins in vitro and in vivo. Materials and Methods: Eight known steroid saponins were isolated from the rhizome of Paris polyphylla. The LA795 lung adenocarcinoma cell line from mice was chosen to evaluate cytotoxicity by means of MTT assay, and to study apoptosis by means of AnnexinV-FITC/PI flow cytometry. Diosgenin-3-α-L-arabinofuranosyl(1→4)-[α-L-rhamnopyranosyl(1→2)]-β-D-glycopyranoside (compound 1), the main steroid saponin of Paris polyphylla, and diosgenin (Dio), the aglycone of major steroid saponins, were evaluated for antitumor activity on LA795 lung adenocarcinoma in T739 inbred mice. Results: The steroid saponins showed remarkable cytotoxicity and caused typical apoptosis in a dose-dependent manner. They were evaluated in vivo by their effect on tumor developed in T739 inbred mice. The oral administration to T739 mice bearing LA795 lung adenocarcinoma of compound 1 and diosgenin significantly inhibited tumor growth, by 29.44% and 33.94%, respectively. HE staining showed that lungs and livers of treated mice underwent various levels of histopathological alterations. It was demonstrated by TUNEL assay that apoptosis rate in tumor cells was increased in comparison to cells in control mice. The 3-O-glycoside moiety and spirostanol structure played an important role in the anticancer activity of steroid saponins, and the number and the variety of glycosides of compounds strongly influenced on their anticancer activity. Conclusion: Rhizoma Paridis saponins showed anticancer activity against lung adenocarcinoma cell line, both in vitro and in vivo, and their effect was dependent on compounds’ structure in a certain degree.